Website-Based E-Learning Information System at the Indramayu Library and Archives Service - Zakiyyatuz Zahra (Manajia: Journal of Education and Management, 2025)
This article presents a comprehensive analysis of the dynamics of E-Learning in the context of higher education and its relevance to the Merdeka Belajar Kampus Merdeka (MBKM) policy. This study also analyzes the strategic initiative of the Indramayu Library and Archives Service (DPA) which launched a Website-Based E-Learning Information System as an inclusive and free community-based non-formal education program. The method used is a qualitative and descriptive-analytical literature review, which focuses on the synthesis of data from scientific journals and academic publications. The results of the study identify four main pillars: (1) The development of E-Learning has evolved from passive CBT to an AI-supported Adaptive, Mobile, and Immersive model; (2) There are significant differences in implementation, where universities emphasize autonomy, specialization, and research, in contrast to the instructional nature of schools; (3) The advantages of E-Learning lie in flexibility, cost efficiency, and increased digital competence, while its disadvantages include challenges in infrastructure access (digital divide) and deficits in social interaction; and (4) As a contribution to Wiralodra University, a blended-flexible strategy, improved lecturer e-Tutor competency, and diversified digital assessments are recommended. Overall, the success of the DPA Indramayu e-Learning system depends heavily on the DPA's ability to address ICT infrastructure challenges and continuously develop an adaptive and interactive curriculum, thus serving as an inclusive solution for enhancing community capacity in the digital age. E-Learning is a transformative catalyst that requires inclusive pedagogy and careful risk management to optimize its full potential in producing competitive graduates in the digital age.